Examining innovation in the Alps at the local scale - Philippe Bourdeau (Revue de Géographie Alpine)
The Pays des Ecrins, which hosted the 2008 Alpine Week, is an emblematic mountain region of the French Alps that has to adapt in the face of numerous endogenous and exogenous crises and changes. Questions relating to creativity and innovation are thus raised in a structural manner and can be seen both as an injunction and a means to developing resources. Based on a review of the path taken by this region over the past twenty years, this paper examines the geo-historical and geo-cultural underpinnings of innovation in a context of local heritage and tourism development.